Aspidistra qijiangensis (Asparagaceae), a new species from Chongqing, China - Luo, Xin-Yan; Xu, Wen-Fen; He, Shun-Zhi (Phytotaxa, 2018)
In April 2017, during an investigation at the Chongqing municipality, Qijiang district, we found some plants of Aspidistra Ker Gawler (1822: 628) with freshly opened flowers widespread on hillside shrub. This species was identified as new for science after studying relevant literature (Lang et al. 1982, 1984, 1999, Li et al. 1988, Wan et al. 1989, Tillich 2006, Tillich et al. 2012, Lin et al. 2013, He et al. 2015, Liang et al. 2016, Zhou et al. 2016, Pan et al. 2016, Vislobokov 2016, Zhong et al. 2016, Wang et al. 2017, Xu et al. 2017) and is described here.